Cloning and characterization of the Escherichia coli gene coding for alkaline phosphatase. - Berg, P E (1981)
The Escherichia coli structural gene for alkaline phosphatase, phoA, and a promoter-like mutant of phoA, called pho-1003(Bin) phoA+, were cloned by using plasmid vectors. Initially, these genes were cloned on deoxyribonucleic acid fragments of 28.9 kilobases (kb). Subsequently, they were subcloned on fragments and 4.8 and then 2.7 kilobases. A restriction map was developed, and phoA was localized to a 1.7-kb region. The promoter end of the gene was inferred by its proximity to another gene cloned on the same deoxyribonucleic acid fragment, proC. The stability of the largest plasmid (33.3 kb) was found to be recA dependent, although the subcloned plasmids were stable in a recA+ strain. Synthesis of alkaline phosphatase directed by the phoA+ and pho-1003(Bin) phoA+ plasmids in a phoA deletion strain was assayed under repressing and derepressing levels of phosphate. These data were compared with the copy numbers of the plasmids. It was found that synthesis of alkaline phosphatase was tightly regulated, even under derepressing conditions: a copy number of 17 enabled cells to synthesize only about twofold more enzyme than did cells with 1 chromosomal copy of phoA+. Enzyme levels were also compared for cells containing pho-1003(Bin) phoA+ and phoA+.